Classroom Management and Initial Teacher Training. a Review Study - Villalta-Paucar, M (EDICIONES UNIV VALPARAISO, 2017)
Classroom management has been documented by decades of research and proposals published mostly in English. The aim of this paper is to analyze formative proposals on classroom management for initial teacher training. We carried out a mixed methodological study that combines qualitative and quantitative analysis techniques for a set of 46 scientific studies published in journals indexed in Scopus and WOS between 2010 and 2016. The main result is that, regardless of whether the formative proposals favor training on effective strategies or cognitive skills to foster classroom management, proposals develop management content focused on behavior control and the organization of classroom instruction. Frameworks on classroom management are discussed.